INNOVATION MANAGEMENT SYSTEM MODEL OF STATE CIVIL SERVICES USING SOFT SYSTEM METHODOLOGY APPROACH - Soesanto, Hari (Natapraja, 2021)
The innovations in the public sector in Indonesia produced by the state civil apparatus have not been fully managed systematically and integrated. Several Ministries and Institutions, as well as Local Governments, have made efforts to facilitate the innovation ecosystem even though there has been no connectivity and innovation platform integration together. The problems that occur in the management of innovation in the public sector are different from those of the private sector, especially in the aspects of the complexity of the problem, uncertainty, and the capacity of bureaucratic innovation. These problems require a different approach to studying them. One approach that is suitable for studying complex, uncertain, unstructured, and involving human social activities is the systems thinking approach, especially the Soft System Methodology (SSM). This study aims to formulate a conceptual model of the innovation management system produced by the state civil apparatus, especially civil servants in Indonesia, through the Soft System Methodology. The research results will be useful for policymakers, especially agencies that have the task and function of encouraging innovation for the government sector (public sector) in Indonesia at both the central and local government levels.